Vertical Land Consolidation For Handling Urban Housing And Slum Settlement Arrangements - Bernadete Nurmawati; KMS Herman; Dewi Iryani; Adi Darmawansyah; Russel Butarbutar (Faculty of Law, Universitas Pekalongan, 2023)
The proliferation of slums in cities with limited land availability calls for regulation on how best to utilize and control Land and initiatives to streamline and improve land use in metropolitan areas through land consolidation. Therefore, the government can use land consolidation to ensure the quality of the urban environment and the social functions of Land. Land consolidation itself is mainly carried out on city properties due to the high concentration of people and lack of planning that characterizes many urban environments. In urban slum programs, vertical land consolidation is an alternative land supply to reorganize slums. By reorganizing who owns what, where it can be used, and how it can be used, land consolidation is carried out to enhance natural resource conservation and improve environmental quality through community involvement and public use of previously privately owned Land. Community participation is a major part of the framework for improving the quality and quantity of land functions. Vertical land consolidation can serve as a useful solution to urban problems such as housing affordability and density. By consolidating Land vertically, more housing units can be built in a smaller area, providing more affordable housing options for residents. In addition, vertical land consolidation helps reduce urban sprawl and results in more sustainable and livable cities. This paper uses normative legal research techniques, including research into applying positive law and legal principles or norms.